Review of the Implementation of Online Auction Service (e-auction) for Dependent Right at the state Wealth and Auction Service Office (KPKNL) Bandar Lampung - Afriyan Arqi Putra Pradana (Cita konsultindo, 2025)
Online auction (e-auction) is an innovation in the auction system carried out through the internet to increase efficiency and transparency. This study aims to analyze the implementation of online auction services for dependent rights at the Bandar Lampung State Property and Auction Service Office (KPKNL) and identify the obstacles faced in its implementation.The research method used is normative and empirical juridical, with a legal approach based on the Minister of Finance Regulation (PMK) No. 213/PMK.06/2020 as well as observations and interviews with auction officials. The results of the study show that the online auction is carried out through the Indonesian Auction Portal (www.lelang.go.id) with established procedures, starting from registration to taking the certificate of dependent rights.However, there are several obstacles in its implementation, such as limited technology infrastructure, suboptimal data security, lack of digital literacy of participants, and unbalanced competition due to differences in access to technology.To increase the effectiveness of online auctions, it is necessary to improve infrastructure and system security, socialization to the public, and strict supervision to ensure transparency and public trust. With these steps, it is hoped that the e-auction system for dependents can run more efficiently and provide wider benefits for the community.